APPLYING INTRODUCTION, BODY, LANGUAGE STRATEGY TO ENRICH THE STUDENTS WRITING ABILITY - Adriani Jihad (EDU RESEARCH, 2023)
The objective of this research is aimed to know the application of Introduction, Body, Language Strategy in improving students’ writing ability at the first-grade students of SMA YP PGRI 2 Makassar. This research used a pre-experimental method with one group pretest and posttest design. The population of this research was the first grade of SMA YP PGRI 2 Makassar. The total sample was 20 students. The result of the data showed that the mean score of post-tests was greater than the pre-test (85.15>56.2) and the t-test value was greater than the t-table value (2.339>1.729) at the level of significant 0.05. It can also prove that the result of the five components of writing, where the post-test result was higher than the pre-test. So, it can be concluded that from the score of the five components of writing on post-test (Content, vocabulary, language use, organization and mechanic) was greater than the score of the five components of writing on pre-test. So, it concluded that Introduction, Body, Language Strategy improves the students’ writing ability.